The city of mist : stories - Ruiz Zafón, Carlos, 1964-2020 (Harper, an imprint of HarperCollinsPublishers, 2021)
Presents a complete collection of the author's short stories, some of which were not previously published, featuring such characters as a boy who decides to become a writer to impress the rich girl he has fallen in love with and an architect with plans for an impregnable library.